SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PESERTA UNTUK MENGIKUTI PROSES PELELANGAN BARANG DAN JASA PADA PEGADAIAN MENERAPKAN METODE EXPROM II - Pratidina, Ageng Puspita; Mesran, Mesran; Ginting, Permanan (STMIK Budi Darma, 2017)
Auction of goods and services is a common thing done by the Pawnshop and this is done by the Pawnshop if the pawnshop is no longer able to pay off the mortgaged goods. Under the mortgage law, the prospective borrower has an obligation to surrender his property as collateral to the pawning party. The law also contains the purchase of the right to the remuneration to make a sale (auction) on the guarantee if the deadline for the loan is exhausted and the borrower can not redeem his guarantee. The process of determining the eligibility of the participants is still conventional so it requires a good decision support to choose the winning bidder. The application of EXPROM II method in information system based on decision support system is able to determine the eligibility of bidders.